Rural development and social change - Prasad, R. R.; Rajanikanth, G. (New Delhi : Discovery Pub. House, 2006)
Contributed articles presented at the NIRD Foundation-day Seminar on "Rural Development and Social Change" held on 9-10 Nov. 2005; with reference to India.
Series statement from jacket.
Keywords: Rural development -- Congresses; Social change -- Congresses